Immune checkpoint inhibition with PD-1 inhibitor induces cardiac dysfunction without overt myocarditis in C57BL/6J mice. (10th June 2022) - Gergely, T; Kucsera, D; Toth, VE; Petrovich, B; Agg, B; Onodi, ZS; Ruppert, M; Radovits, T; Merkely, B; Ferdinandy, P; Varga, ZV
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 Research and Innovation Programme under grant agreement no. 739593 "Semmelweis 250+ Kiválósági PhD Ösztöndíj" (EFOP-3.6.3-VEKOP-16-2017-00009) Gedeon Richter Talentum Foundation's scholarship Background: Immune checkpoint inhibitors have revolutionized the treatment of several form of malignancies (including metastatic melanoma) by enhancing the cytotoxic effects of T cells against cancer cells. Cancer cells evade immune surveillence by increasing the expression of T cell inhibitory molecules, also known as immune checkpoints, such as programmed cell death-1 (PD-1). Pharmacological inhibition of these molecules by immune checkpoint inhibitors (ICI) will enhance the antitumor activity of T cells. However, enhanced T cell activity may cause immune related adverse effects, including cardiotoxicity. Aims: We aimed to investigate the effect of PD-1 inhibition on cardiac function and the underlying mechanisms in mice. Methods: 8-10 weeks old C57BL6/J mice were treated with isotype control or anti-PD-1 antibody for 2 or 4 weeks. Cardiac function and morphology was assessed by echocardiography and histology, while the transcriptomic changes were analyzed via RNA sequencing. Nitrosative stress in the heart was assessed by immunohistochemistry and qRT-PCR. Inflammatory gene expression alterations were determined by qRT-PCR in the heart and thymus. Results: Small animal echocardiography revealed cardiac dysfunction even after 2 weeks of anti-PD-1 treatment, with distinct transcriptomic changes. Nitrosative stress was found to be elevated in the myocardium due to anti-PD-1 treatment, however, histological and qRT-PCR analysis did not reveal T cell infiltration into the myocardium and only mild inflammation was seen in the heart. In contrast, inflammatory gene expression was significantly enhanced in the thymus of anti-PD-1-treated animals, where interleukin-17 showed the most prominent increase. Conclusions: These findings characterize cardiac dysfunction as a form of ICI-induced cardiotoxicity, which may be mediated by increased thymic inflammatory activation and cytokine production.